The Effect of Plasticine Media on Alphabet Recognition in 4-5 Year Old Children in Kindergarten - Aprilia, Putri Cika; Febriyanti; Fahmi (UNIB Press, 2025)
Alphabet recognition is an essential skill in students' development; therefore, it requires greater attention from parents and teachers. This study aims to determine the effect of plasticine media on letter recognition in early childhood at Baiturrahman Sako Islamic Kindergarten, Palembang. This study uses a quantitative approach with a one-group pretest-posttest design and involves 15 children as samples selected by the purposive sampling method. The instrument used is an observation sheet that has been tested for validity and reliability with valid and reliable results. The research procedure includes administering a pretest and providing treatment through plasticine-based learning. A posttest was administered to assess treatment outcomes; the data were analyzed using a t-test, which showed a significant increase in scores (p < 0.001). These results demonstrate that plasticine media affect letter recognition in children aged 4-5 years.